Multi-Zone Ice Accretion and Roughness Models for Aircraft Icing Numerical Simulation (Advances in Applied Mathematics and Mechanics, 2018)
A mathematical multi-zone ice accretion model used in the numerical simulationof icing on airfoil surface based on three water states, namely, continuous film,rivulets and beads is studied in this paper. An improved multi-zone roughness modelis proposed. According to the flow state of liquid water and film flow, rivulets flowgoverning equations are established to calculate film mass distribution, film velocity,rivulet wetness factor and rivulet mass distribution. Force equilibrium equations ofdroplet are used to establish the critical conditions of water film broken into rivuletsand rivulets broken into beads. The temperature conduction inside the water layer andice layer is considered. Using the proposed model ice accretion on a NACA0012 airfoilprofile with a $4^◦$ angle of attack under different icing conditions is simulated. Differentice shapes like glaze ice, mixed ice and rime ice are obtained, and the results agree wellwith icing wind tunnel experiment data. It can be seen that, water films are formed onthe surface, and heights of the films vary with icing time and locations. This results inspatially-temporally varying surface roughness and heat transfer process, ultimatelyaffects the ice prediction. Model simulations indicate that the process of water filmformation and evolution cannot be ignored, especially under glaze ice condition.